2020
DOI: 10.3844/ajeassp.2020.563.583
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison for Compression of PLA Specimens Printed in In-Plane and Out-of-Plane Directions

Abstract: The present work proposes an experimental comparison between the in-plane and out-of-plane compressive behaviors of 3D printed PolyLactic Acid (PLA) specimens. These specimens are produced via the Fused Deposition Modeling (FDM) technique by using two different printing directions: the first printing direction in the xz plane allows experimental compression tests in the out-of-plane direction; the second printing direction in the xy plane allows experimental compression tests in the in-plane direction. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, the observed changes are not linear in nature. The recorded values differ 2-to 2.5-fold from those that can be found, for example, in [23,24]. Once again, this is most probably caused by the effect of the selected fill ratio.…”
Section: Results Of Static Testsmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the observed changes are not linear in nature. The recorded values differ 2-to 2.5-fold from those that can be found, for example, in [23,24]. Once again, this is most probably caused by the effect of the selected fill ratio.…”
Section: Results Of Static Testsmentioning
confidence: 55%
“…The authors of [22] determined the value of this coefficient at approximately 1750 MPa, without registering any significant effect connected with flat and upright printing orientations (cylindrical sample of the diameter of 12.7 mm and height of 25.4 mm, with the compression velocity of 1.3 mm/min). Research described in [23], on the other hand, demonstrated compression modulus E c values of approximately 2578 MPa for out-of-plane compression tests and approximately 2029 MPa for in-plane compression tests (rectangular samples, base side length 12.7 mm, height 40 mm). These were similar to values determined in [24].…”
Section: Results Of Static Testsmentioning
confidence: 97%